2003
DOI: 10.1557/proc-785-d9.1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Actuating System Based on a Composite of Single-Walled Carbon Nanotubes and an Ionomeric Polymer

Abstract: We report the fabrication and characterization of a novel composite material based on single walled carbon nanotubes (SWNT)s and the ionomeric polymer Nafion. SWNTs were airbrushed from a chloroform suspension onto both sides of a Nafion membrane (180 µm) and the electromechanical properties of the composite material were explored. The outer layers of carbon nanotubes acted as electrodes in order to pass electrical current through the system while the mechanical response was monitored. Under this design, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Compared to Levitsky et al (2004), SWNT did not increase the stiffness in the actuators relative to RuO 2 -based transducers. This leads to a lower bandwidth in the SWNT and hybrid actuators.…”
Section: Mechanical Dampingmentioning
confidence: 75%
See 2 more Smart Citations
“…Compared to Levitsky et al (2004), SWNT did not increase the stiffness in the actuators relative to RuO 2 -based transducers. This leads to a lower bandwidth in the SWNT and hybrid actuators.…”
Section: Mechanical Dampingmentioning
confidence: 75%
“…This leads to a lower bandwidth in the SWNT and hybrid actuators. Note that Levitsky et al (2004) used a different electrode and fabrication technique, and the SWNTs were sprayed on the electrode.…”
Section: Mechanical Dampingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Yang et al [17], molecular dynamic studies confirmed that hydrophobic surface properties are dependent on the rootmean-square (RMS) of the surface roughness. Many present and future applications in nanotechnology will require controlling the interaction and assembly of ionomer structures for new membranes [18], enhanced mechanical structures for composites [19], enhanced actuators [20], and structured carbon-ionomer nanocomposites for polymer electrolyte membrane (PEM) fuel cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Initial results by Bennett and Leo and Vidal, et al have demonstrated that using a hybrid ionic polymer-conducting polymer actuator increases the force output and the bandwidth of the transducers 1,9 . Recently, carbon nanotubes-ionomer hybrid actuators have also proved to increase the strain and force of the transducers 10 . Levitsky et al sprayed the nanotubes on a Nafion TM membrane, and reported 0.9mm tip displacement under 3.5V for a 3mm x 20mm water hydrated transducer.…”
Section: Introductionmentioning
confidence: 99%